Radiation engineering analysis of shielding materials to assess their ability to protect astronauts in deep space from energetic particle radiation. (June 2020) - Manning, Bryan; Singleterry, Robert
Abstract: This paper explores the changes in the radiation quantity whole body effective dose equivalent ( E ) caused by galactic cosmic rays (GCRs) by varying position, geometry, material, and thickness of radiation shielding in order to determine possible launch characteristics of a vehicle design. The On-Line Tool for the Assessment of Radiation in Space (OLTARIS) was used to simulate deep space missions lasting 180 or 400 days with a mission radiation surrogate exposure limit of 150 mSv . Previous work used only spherical shielding; however, the shielding geometries investigated in this paper were right circular cylinders and spheres comprised of aluminum, polyethylene, liquid methane, water, and liquid hydrogen. Materials were evaluated individually, in multi-material pressure vessel mock-ups, and personal protection forms for individual astronauts. With single-material shielding, a single launch of shielding material to low Earth orbit (LEO) was possible for all materials for a 180 day mission, but insufficient for a 400 day mission. Multi-material and personal protection forms, as well, were found to be suitable for a 180 day mission, but not for a 400 day mission. Overall, no feasible designs in these analyses were able to meet the surrogate limit and protect an astronaut for 400 days. Highlights: OLTARIS shows a position dependent exposure within a vehicle. Right circular cylinders and spheres show approximately the same exposure. A launch of a material will not exceed 150 mSv effective dose for 180 days. No feasible designs were found for a 400 day mission.